WAKTU MOTILITAS DAN VIABILITAS SPERMATOZOA IKAN MAS (Cyprinus carpio L) PADA BEBERAPA KONSENTRASI LARUTAN FRUKTOSA - Hidayaturrahmah Hidayaturrahmah (Bioscientiae, 2007)
The research was aimed to reveal the effect of fructose consentration on the motility and viability time of carp’s spermatozoa, and to determine the optimal consentration of fructose. A completely randomized design was applied with 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, and 4% fructose concentrations. Undiluted semen and aquades-diluted semen were used as controls. Fast progressive and slow progressive motility of spermatozoa were recorded as well as the viability time (in minutes) of the spermatozoa.   The results showed significant difference in motility and viability time of spermatozoa with different concentrations of fructose. The optimal average concentration was 3%, resulting in fast progressive motility of 11 seconds, slow progressive motility of 165 seconds, and viability time of 4 hours 46 minutes. The increase in motility and viability time were assumed to be related to the use of  fructose as energy source and nutrition for spermatozoa.